Inter/Intra-Observer Reproducibility of Gleason Scoring in Prostate Adenocarcinoma in Iranian Pathologists - Hassan Hosseinzadeh; Mohammadreza Bakhshandeh; Ali Ahmadi; Hedieh Moradi-Tabriz; Sara Sheikhbahaei; Alipasha Meysamie; Alireza Abdollahi (Urology Journal, 2012)
PURPOSE: To measure the level of inter/intra-observer reproducibility among pathologists as far as Gleason scoring of adenocarcinoma of the prostate is concerned. MATERIALS AND METHODS: A total of 101 prostate biopsy slides, diagnosed with adenocarcinoma of the prostate by five pathologists from different education centers, were exposed to Gleason scoring. Two months later, the slides were re-examined by three of the same pathologists. Thereafter, the kappa was calculated for the data provided in the first and second reports of each pathologist and compared between pathologists. RESULTS: Inter-observer reproducibility was inappropriate, but intra-observer diagnostic reproducibility was almost perfect with a corresponding percentage of agreement of 85.2%. CONCLUSION: The inter-observer reproducibility was poor.